Association of neuropathic limb pain in multiple sclerosis with cognition, behaviour, and measures of brain structure: a case-control MRI neuroimaging study. (25th February 2016) - Foley, Peter; Pernet, Cyril; Valdes-Hernandez, Maria; Margeviciute, Ramune; Roberts, Neil; Kong, Yazhuo; Sellar, Robin; Colvin, Lesley; Weir, Christopher; Bak, Thomas; Chandran, Siddharthan; Tracey, Irene; et al.
Abstract: Background: Neuropathic limb pain commonly affects people with multiple sclerosis but is incompletely understood. Emotional, psychological, and executive functions, acting via brainstem pathways, have been linked to pain modulation. We aimed to compare these functions, as well as MRI measures of brain structure, in adults with multiple sclerosis with and without pain. We hypothesised that, in those with pain, the ability to suppress or reappraise stimuli would be reduced, with altered lesion distribution or grey matter volume loss. Methods: Adults with relapsing remitting multiple sclerosis with and without neuropathic limb pain were recruited from clinic; they were matched for sex, age, disability, duration of multiple sclerosis, and education. None used strong opioids. Participants underwent targeted psychological and neuropsychological assessment, with 1 mm 3 MPRAGE (magnetisation-prepared rapid gradient-echo), T2, and FLAIR (fluid attenuation inversion recovery) brain MRI at 3 Tesla. Distribution of multiple sclerosis lesions was analysed by semi-automated segmentation, probability mapping, and permutation analysis. Grey matter volume was analysed by voxel based morphometry (VBM). Significance thresholds adjusted for multiple comparisons. Findings: We recruited 31 adults with pain and 16 matched controls. Participants with pain more often used adjuvant analgesics than did controls (22/31 [71·0%] vs 3/16 [18·8%], p=0·002). They described more depressive symptoms (Hospital Depression Scale median 5·0 [IQR 2·0–8·5] vs 1·5 [0·0–6·0], p=0·005), fatigue (Fatigue Severity Scale 51·0 [43·5–56·5] vs 33·0 [26·8–43·8], p=0·003), and catastrophising (Pain Catastrophizing Scale 16·0 [12·5–25·0] vs 8·5 [0·8–15·0], p=0·004). Patients with pain displayed impaired reappraisal (Delis Kaplan card test set 1 recognition scores 12·0 [8·0–20·0] vs 24·0 [21·0–24·0], p<0·0001). Multiple sclerosis lesion volume overall did not significantly differ between groups. Brainstem lesion volume was significantly higher in those with pain (p=0·0049). VBM did not reveal altered cortical volumes between groups. Interpretation: This cross-sectional study suggests that neuropathic limb pain in relapsing remitting multiple sclerosis is associated with specific emotional, psychological, and executive dysfunction, and brainstem location of lesions. Adjuvant analgesics can affect neuropsychological performance, but are less likely to affect imaging measures. Longitudinal or interventional studies could clarify any mechanistic or therapeutic implications of our findings. Funding: Anne Rowling Regenerative Neurology Clinic, University of Edinburgh (Rowling Scholar scheme); University of Edinburgh (Doreen Maguire endowment).